MEDIATISASI AGAMA (PEMBINGKAIAN MEDIA KOMPAS.COM TERHADAP ISU PEMERKOSAAN OLEH OKNUM PENGASUH PESANTREN) - Syihabul Furqon; Busro Busro (Fakultas Ushuluddin dan Dakwah UIN Raden Mas Said Surakarta, 2017)
Framing analysis, methodically is used to dissect discourse impulses that leading to stigma crystallization. Media frames an issue by using language tools and plays a subconscious role in the attitude and understanding of society. Although, basically, every media does framing, but the problem that comes next is when this framing becomes an interest to postulate the lame proposition socially and logically. This research efforts to analyze in narrative about how religion is mediated by Kompas.com, through framing information issue about the Rape by the Board of Pesantren issue in framing analysis of Zhongdang Pan and Gerald M. Kosicki. In conclusion, the Kompas electronic media framing gives rise to a certain tendency toward the negative stigma of pesantren in the public through a narrowing of news content in the media, especially from the interpretation and reporting analysis that revolves around closed syntactic and syntagmatic interactions.